O processo formativo de um Programa de Residência Multiprofissional em Saúde da Família na ótica de egressos. - Farias, Évelyn (2023)
Since the legal creation and implementation of the Unified Health System in the country, in 1988, the training of human resources in health is part of its attributions. The training of qualified professionals is a necessity, and so the development of Multiprofessional Residency Programs in Health, whose focus is on in-service training, promoting reflection and problematization through tools such as Continuing Education in Health, has been an important strategy. One of these programs is located in the municipality of Cascavel-PR and its actions are focused on the Family Health Strategy model. Based on this context, we sought to problematize the training promoted by the Multiprofessional Residency Program in Family Health in Cascavel-PR. The objective of this problematization was to verify the real instrumentalization of the graduates for professional performance in Primary Health Care, according to the principles of the Unified Health System. It is assumed that the formation of the Multiprofessional Residency Program in Family Health, despite being a recent experience in the local reality, is contributing positively to the qualified performance of its graduates in Primary Health Care according to the principles of the Unified Health System. The general objective of the study is to evaluate the formative process of a Multiprofessional Residency Program in Family Health from the perspective of the graduates. This is an exploratory-descriptive case study, with a qualitative approach. The data were collected by means of semi-structured interviews with all the graduates who finished the formative process in the residency program in question, with the exception of those who refused to participate in the research. Seventeen graduates were interviewed, including nurses, dentists, and social workers who graduated between 2020 and 2022. The interviews took place between June 16 and July 21, 2022, lasted an average of 28 minutes and were conducted via video calls made on the online platforms Google Meet and Microsoft Teams, which were recorded and transcribed, being used Bardin's content analysis to treat the results. The data were presented in the form of articles, the first of which used the SWOT matrix to analyze the potentialities and weaknesses of the Multiprofessional Residency Program in Family Health. The potentialities were: a) strengthening of the professional intervention in Primary Health Care; b) performance in different practice settings in the learning process, which allowed the interaction of residents with different teams, preceptors and Units; c) the multiprofessional practice provided in the Multiprofessional Residency Program in Family Health and its contribution to the development of skills inherent to each professional category involved in the training and d) intentional and systematized preparation for performance in the Unified Health System. The weaknesses of the teaching-learning process of the Program are related to the contents and methodological routes of theoretical activities; the lack of multidisciplinary interaction and activities of Continuing Education in Health; the lack of definition of the roles of coordinator, tutors and preceptors; the difficulty of insertion in the world of work; and the devaluation of trained professionals. The second article presents the participants' motivations for joining the Program, which are: the search for improving and deepening knowledge in public health, overcoming the incipient formation of the undergraduate course in terms of preparation to work in Primary Health Care, the experience in practice of the concepts learned in the undergraduate course, and the possibility of a paid job. This second article also addresses the graduates' experiences in the world of work after graduation. Article three addresses the effects of the Covid-19 pandemic on the training offered, and highlight the intense participation of residents in planning and assistance actions in this period, as well as the possibility of greater contact with medical residents and the multiprofessional residency itself. On the other hand, due to sanitary restrictions, there was a loss in theoretical classes and activities of Continuing Education in Health and Health Education. Given the results, it can be inferred that the Multiprofessional Residency Programs in Health are fertile spaces for the improvement of human resources in health with a view to acting in the Unified Health System, enabling the development of multiprofessional and interdisciplinary actions. However, there is still a need to strengthen the internal aspects, such as greater preparation of preceptors and tutors and more assertive conduction of theoretical classes, and, with respect to the insertion of graduates in the world of work, it points to the importance of creating mechanisms to facilitate entry into the Unified Health System and the granting of financial incentives for residents to remain linked to it.